Empowering Micro Enterprises through the Bondowoso Makmur Program by Baznas Bondowoso: A Case Study of Local Economic Development - Hermanto, Annisa Ramadhani; Titisari, Purnamie; Amijaya, Rachmania Nurul Fitri; Endut, Wan Anisah (Jurnal Internasional Ekonomi Islam, 2025)
Introduction: Microenterprises play a significant role in the Indonesian economy. However, they often face obstacles, including limited capital, market access, and management skills. In this context, zakat institutions such as the National Amil Zakat Agency (BAZNAS) become very relevant in supporting their development. Objective: This study discusses micro-businesses' problems in the Bondowoso District, including the lack of capital. Bondowoso Regency has limitations in capital, so the Badan Amil Zakat Nasional (BAZNAS) meets the need for productive zakat assistance. Method: The research used is qualitative with a phenomenological approach. Data collection techniques include observation, interviews, and documentation. Result: The results show that the program's distribution process, including data verification, feasibility surveys, and monitoring, has positively impacted mustahik businesses, increasing turnover, profits, production capacity, and customer base, though full development has yet to be achieved. Implication: This article emphasises the important role of institutions in easing the burden on micro-entrepreneurs; such support can alleviate poverty.